Quality of Life in Rural Communities: Residents Living Near to Tembeling, Pahang and Muar Rivers, Malaysia - Idris, Khairuddin; Mohamed Shaffril, Hayrol Azril; Md. Yassin, Sulaiman; Abu Samah, Asnarulkhadi; Hamzah, Azimi; Abu Samah, Bahaman (PLOS ONE, 2016)
The main aim of this study is to identify the quality of life (QoL) among communities residing near the Tembeling, Pahang and Muar Rivers in Malaysia. This quantitative study used a constructed questionnaire as main tool to collect data on the QoL of river communities. A total of 240 villagers were selected as respondents. The results indicated that the dimensions of settlement, safety, involvement and social relationships, as well as education scored highest, while dimensions of physical environment, financial and job security yielded moderate scores. Dimensions of infrastructure facilities yielded a low mean score. Recommendations are provided, in the hope that our results may be useful for strategies that could enhance QoL of these river communities.